Knowledge and practice on medication adherence among Type II diabetes mellitus patients - Jamaludin, Thandar Soe Sumaiyah; Mohammad, Nurfatihah Masrurah; Hassan, Masmunaa; Nurumal, Mohd. Said (Elsevier, 2021)
This study aimed to survey the level of knowledge and practice on medication adherence among Type II diabetes mellitus (DM) patients. A cross-sectional study was conducted with a total of 220 DM patients by using a convenience sampling method. It was found that 64.5% of studied participants have a high level of knowledge with good practice toward medication adherence. There was a significant association between sociodemographic characteristics with the level of knowledge and practice toward medication adherence. This study finding provides information to health care providers to improve their patient’s care by playing their important role in promoting the importance of knowledge on medication adherence for a better quality of life to the DM patients. Not only a physician but also the nurse could enhance health education for their patient on medication adherence during the follow-up appointment.